Endosperm and Seed Transcriptomes Reveal Possible Roles for Small RNA Pathways in Wild Tomato Hybrid Seed Failure. (19th May 2021) - Florez-Rueda, Ana Marcela; Fiscalini, Flurin; Roth, Morgane; Grossniklaus, Ueli; Städler, Thomas
Abstract: Crosses between the wild tomato species Solanum peruvianum and Solanum chilense result in hybrid seed failure (HSF), characterized by endosperm misdevelopment and embryo arrest. We previously showed that genomic imprinting, the parent-of-origin–dependent expression of alleles, is perturbed in the hybrid endosperm, with many of the normally paternally expressed genes losing their imprinted status. Here, we report transcriptome-based analyses of gene and small RNA (sRNA) expression levels. We identified 2, 295 genes and 387 sRNA clusters as differentially expressed when comparing reciprocal hybrid seed to seeds and endosperms from the two within-species crosses. Our analyses uncovered a pattern of overdominance in endosperm gene expression in both hybrid cross directions, in marked contrast to the patterns of sRNA expression in whole seeds. Intriguingly, patterns of increased gene expression resemble the previously reported increased maternal expression proportions in hybrid endosperms. We identified physical clusters of sRNAs; differentially expressed sRNAs exhibit reduced transcript abundance in hybrid seeds of both cross directions. Moreover, sRNAs map to genes coding for key proteins involved in epigenetic regulation of gene expression, suggesting a regulatory feedback mechanism. We describe examples of genes that appear to be targets of sRNA-mediated gene silencing; in these cases, reduced sRNA abundance is concomitant with increased gene expression in hybrid seeds. Our analyses also show that S. peruvianum dominance impacts gene and sRNA expression in hybrid seeds. Overall, our study indicates roles for sRNA-mediated epigenetic regulation in HSF between closely related wild tomato species.